PERGESERAN MABBACA DOANG ALLEPPERENG DI DESA CONGKO SULAWESI SELATAN - Ramdhana, Sagita; Rusdi, Rusdi (Indonesian Journal of Applied Geography, 2024)
This article discusses the Ma’baca Doang Alleppereng tradition in the Congko community, South Sulawesi. This article departs from the current problem in Congko Village, where various traditions are being abandoned, including the Ma’baca Doang Alleppereng tradition. Ma’baca Doang Alleppereng is a tradition of reading prayers during Eid which is routinely carried out by the Bugis community. This article aims to explain the procedures for carrying out the Ma’baca Doang Alleppereng tradition and various traditional values that are starting to disappear. This study uses a descriptive approach. Data were obtained through observation, literature study and interviews with the community, To Matoa (elderly) and Pabbaca (Mosque Faith, Pabbaca descendant, people who are considered fluent in reading the Al-Quran). The results of this study indicate a shift in the procedures for implementing Ma’baca Doang Allepereng in Congko Village. This is caused by (1) the factor of the entry of Islam in Soppeng Regency which caused a change in the procession of implementing Ma’baca Doang Alleppereng, such as readings that use local languages are now adjusted to the readings self-contained in the Al-Quran; (2) Factors in the development of science and technology that affect the ease of obtaining information, emergence of individual characteristics, emergence of social tensions and emergence of contradictions or conflicts. As a result, the meaning and values of the Ma’baca Doang Alleppereng tradition are in danger of being lost.